Qualitative analysis of the diet of a probabilistic sample of schoolchildren from Florianópolis, Santa Catarina State, Brazil, using the Previous Day Food Questionnaire Análise qualitativa da dieta de amostra probabilística de escolares de Florianópolis, Santa Catarina, Brasil, com o uso do Questionário Alimentar do Dia Anterior - Maria Alice Altenburg de Assis; Maria Cristina Marino Calvo; Emil Kupek; Francisco de Assis Guedes de Vasconcelos; Vanessa Caroline Campos; Manuella Machado; Filipe Ferreira da Costa; Dalton Francisco de Andrade (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
A qualitative evaluation of the diet of a probabilistic sample of 7-10 year old schoolchildren (n = 1,232) from Florianópolis (southern Brazil) was carried out by analyzing compliance with recommendations from the Brazilian Food Guidelines. The strengths and limitations of the Previous Day Food Questionnaire (PDFQ) are also presented. Frequencies of intake were defined as how many times per day the food group was reported on the PDFQ. The percentages of schoolchildren who met the minimum recommendations and who ate foods that were not recommended in the guidelines were compared for boys versus girls, private versus public school and by family income level. Although most of the children complied with the guidelines regarding consumption of meat/fish, dry beans, sweets, and eating three meals and two snacks, only 6.5% of the children met the recommendations for cereals, and 15% for fruit and vegetables. The PDFQ was confirmed as a practical and cost-effective method for the evaluation of compliance with health promotion targets. Avaliação qualitativa da dieta de uma amostra probabilística de escolares de 7-10 anos (n = 1.232) de Florianópolis, Santa Catarina, Brasil, é apresentada por meio de uma análise da concordância com as recomendações do guia alimentar para a população brasileira. Os aspectos positivos e as limitações do Questionário Alimentar do Dia Anterior (QUADA) são também discutidos. As freqüências de consumo foram definidas em vezes por dia que os grupos de alimentos foram relatados no QUADA. As porcentagens de escolares que atingiram as recomendações mínimas do guia e que consumiram alimentos não recomendados foram comparadas entre os sexos, tipo de escola (pública versus privada) e nível de salário familiar. A maioria das crianças apresentou concordância com o guia para o consumo de carnes/peixes, feijão, doces e realização de três refeições e dois lanches; somente 6,5% atingiram as recomendações dos cereais e 15% das frutas e hortaliças. O QUADA confirmou-se como um método prático e de custo-efetividade para a avaliação da concordância com metas de promoção de saúde.